HUBUNGAN IMUNISASI RUTIN LENGKAP TERHADAP PERTUMBUHAN DAN PERKEMBANGAN ANAK USIA 36-59 BULAN DI INDONESIA (ANALISIS DATA RISKESDAS TAHUN 2018) - Lisa M; Amrina Rosyada (Dian Nuswantoro Semarang, 2022)
WHO reports that 28.7% of children under five experience impaired growth and development in Southeast Asia. In Indonesia, the complete basic immunization coverage has not reached the target. It is 57.9%. This study aims to analyze the relationship of complete routine immunization with the growth and development of children in Indonesia. The method of data analysis uses a complex sample survey from Riskesdas 2018 with a cross sectional research design. Sampling used multistage random sampling with a sample of 10462 respondents. The results showed that the prevalence of children with abnormal growth was 27.1% and doubtful development was 39.9%. The results of multivariate analysis showed that there was no significant relationship between complete routine immunization and child growth (p value = 0.266; PR = 1.088; 95%CI = 0.9381.261) after controlling by variable sex and there was no significant relationship between complete routine immunization with child development (p value = 0.131; PR = 1.110; 95%CI = 0.969 -1.271) after controlling by variable access to health care facilities. Parents should provide complete routine immunizations, give an adequate food intake, maintain a clean environment and routinely bring children to the posyandu to monitor children's growth and development.